A arquitetura curricular e o Projeto Político Pedagógico das escolas do/no campo em Itaúna/MG: o chão nosso de cada dia - Andrade, Tânia (2023)
This thesis deals with the relations between the curricular architecture and the Pedagogical Political Project of seven rural schools in the municipality of Itaúna, in the state of Minas Gerais (MG), Brazil, from the perception of people that make up the school community. The problem that triggers the research is: the right to a good enough education is not being carried out in schools of/in the rural areas. The guiding question of the research is: What is it and how to become a good enough rural school? The object of the research is the Pedagogical Political Project of the rural schools considered as a component of what is named, in this work, “curricular architecture”. The hypothesis rests on the legitimacy of the principles of the rural school, which, for the most part, are explicit in documents, but do not materialize in the school space, namely: guarantee of the collective protagonism of the school community; democratic school management; and articulation of curricular practices with a school and society project based on, with and for the rural people. The objective of the study was to understand how far the curricular architecture defines the “way of being” of the whole school and, in this perspective, how the school community transits, referenced by the Pedagogical Political Project of the school, in the scope of the curricular architecture, so that the school becomes a good enough rural school. Methodologically, the investigation was carried out using a qualitative approach and the procedures used for data collection were non-directive interviews and semistructured questionnaires directed to the school community, which were analyzed and understood through a dialog with the studies of Bardin (2004), Chizzotti (2017) and Lüdke and André (1986). The theoretical framework is based on the contributions of authors dedicated to the study of education of/in the rural area, more specifically in the works of Arroyo (2002, 2004, 2007, 2011, 2020), Caldart (2011, 2012) and Souza (2008, 2016, 2018). For general support, it was used as bibliographic references: bibliographical productions on rural education and on education of/in the rural area, bibliography on historical contexts; laws and regulations; public policies; experiences of curricula; reports of experiences of democratic management and teacher training; and experiences of Pedagogical Political Projects. The results of the research point to the need to broaden and deepen investigations about the curricular architecture of schools in rural areas, about their democratic school management and about a specific teacher training for education of/in the rural area, since these elements largely contribute to its legitimacy, in order to transform them into a good enough rural school